1980
DOI: 10.1172/jci109848
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-sensitive Enteropathy

Abstract: A B S T R A C T We previously developed an in vitro organ culture system in which gluten exerts a toxic effect on intestinal mucosa of patients with active gluten-sensitive enteropathy. Gluten generally inhibits the epithelial cell maturation of intestinal biopsy specimens that otherwise occurs if the tissue is cultured for 24-48 h in a gluten-free medium. However, small intestinal mucosa from 15-20% of patients with proven gluten-sensitive enteropathy fails to manifest the expected gluten-induced damage in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…In vivo and in vitro studies have identified α-gliadins as a major source of toxicity for CD patients 26272829. Our study confirms that these proteins are also a major focus of the intestinal T cell response to gluten.…”
Section: Discussionsupporting
confidence: 79%
“…In vivo and in vitro studies have identified α-gliadins as a major source of toxicity for CD patients 26272829. Our study confirms that these proteins are also a major focus of the intestinal T cell response to gluten.…”
Section: Discussionsupporting
confidence: 79%
“…Cultured intestinal epithelial tissues from celiac patients have been tested also by Jos et al (36)(37)(38) who showed that peptides derived from purified gliadin fractions including a-, P-, 7-, and w-gliadins were toxic in celiac disease. These results were consistent with those by Hekkens et al (32) who demonstrated that an a-gliadin fraction, coded A-gliadin (10,49), was capable of producing changes in epithelial tissue characteristic of celiac disease when instilled directly into the small intestine of celiac patients and with those by Falchuk et al (19) showing that this fraction had adverse effects on biopsied intestinal epithelium. Huge and co-workers (24)(25)(26) have developed a morphological, morphometric, and biochemical assessment of human duodenal biopsies from celiac patients maintained in organ culture and have tested with this in vitro system several gliadin fractions including a-gliadin and Frazer's fraction I11 and subfractions.…”
supporting
confidence: 92%
“…Falchuk et al (19,20) have proposed the organ culture of human small intestinal biopsies as an in vitro model of celiac disease. Jejunal specimens obtained from patients with active enteropathy show morphological and biochemical improvement when cultured in a gliadin-free medium.…”
Section: (Pediatr Resmentioning
confidence: 99%
“…They have also shown that cortisol appears to provide some protection from the effects in vitro of GFIII on untreated coeliac mucosa, suggesting that cortisol is acting through its immunosuppressant effects [42]. They have more recently shown that the response of the untreated coeliac mucosa in vitro to GFIII is related to the HLA B8 status of the patients, once again providing a link with immunopathological mechanisms [43].…”
Section: Human Mucosamentioning
confidence: 98%